What makes full-time employed women satisfied with their working hours? - Marit Rønsen; Ragni Hege Kitterød (Statistics Norway, Research Department, 2010)
In spite of extended parental leaves, tremendous improvement in day-care availability, and a cultural climate that is supportive of women's full-time work, Norwegian women still have one of the highest female part-time rates in Europe. Longer working hours among women would clearly alleviate the lack of labour in many sectors of the economy, but this reserve may be difficult to mobilise as previous research have shown that large proportions of female full-time workers are discontent with their working hours. In this article we examine whether this is true even today, and identify factors that may facilitate or impede working-hours satisfaction among female full-timers based on recent data from the Norwegian Labour Force Surveys. Contrary to past research, we find that most women are satisfied with their full-time hours. Still, young children in the household are a strong deterrent of full-time contentment, as is long working hours for the spouse, if women are married. Full-time contentment also varies with occupation, but the main job-deterrent seems to be non-standard working hours such as shift and rota.
Keywords: J22; J24; J28; 330; Female labour supply; working-hours preferences; working-hours contentment; full-time work